(3QSGdI GdcdfHhi aj GdJbOes - (3ESeGYjd GdcdfHhj,J (B1205 (3g` s ((3aGVd GdcdfHhi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje EYde Cf GdJbOe jbGd Ydi NeSI CTjGA GdChd GdJbOe HGdReGf s
(3BNQgG (B:s
(3aGdJbOe HGdQJHI CNU ef GdJbOe HGdTQa aGdJbOe NeSI JeJ GdQSGdI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs